The Baseline, Clinical, and Laboratory Parameters of Breast Cancer Subjects Infected with COVID-19 in Medan, Indonesia - Siregar, Kamal Basri; Azrah, Arjumardi; Aryanti, Citra (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Cancer patients may be susceptible to COVID-19 infection due to decreased immune status. Breast cancer is the most common cancer in Indonesia, still has high admission, which increasing the risk of exposure to COVID-19. AIM: Thus, this study aimed to identify hospitalized breast cancer patients diagnosed with COVID-19 infection 1 year after the pandemic. METHODS: This is a cross-sectional study that was conducted in the Adam Malik General Hospital in Medan, Sumatera Utara, Indonesia. The enrolled subjects were those who previously histopathologically confirmed with breast cancer and having laboratory-confirmed COVID-19 infection The sources of baseline, clinical, and laboratory data were retrieved from the electronic medical records. Statistical analysis was performed using the SPSS 16.0 software (SPSS Inc., Chicago, IL, USA). RESULTS: A total of 17 female breast cancer subjects with COVID-19 infection were enrolled in this study. Mostly subjects were multiparity, highest education was junior high school, housewife, menopause, diagnosed in Stage IV, had metastasis in lung, and categorized luminal B with invasive cancer of non-special type. Most subjects showed mild clinical and radiological severity of COVID-19 infection. Low leukocyte, high neutrophil-to-lymphocyte, and high platelet-to-lymphocyte counts were significantly differed between alive and death outcome in the subjects. CONCLUSION: The baseline and clinical characteristics of female breast cancer subjects with COVID-19 infection were similar to general characteristics in the population. The parameters of leukocyte, neutrophil-to-lymphocyte, and platelet-to-lymphocyte counts could be a valuable predictive parameters of mortality outcomes.